Examining Evident Interdisciplinarity Among Prides of Lion Researchers - Montgomery, Robert A.; Elliott, Kevin C.; Hayward, Matthew W.; Gray, Steven M.; Millspaugh, Joshua J.; Riley, Shawn J.; Kissui, Bernard M.; Kramer, Daniel B.; Moll, Remington J.; Mudumba, Tutilo; Tans, Eric D.; Muneza, Arthur B.; et al. (Frontiers in Ecology and Evolution, 2018)
Lions (Panthera leo) have experienced dramatic population declines in recent decades and today, inhabit just a fraction of their historic range. The reasons behind these declines are many, but conflict with humans, principally motivated by lion depredation of livestock, is among the most influential. Recent calls within the scientific community have identified that wicked problems like these should be addressed using interdisciplinary approaches. Here we examined the extent to which human-lion conflict research has been interdisciplinary. We conducted an extensive review of the literature and uncovered 88 papers, published between 1990 and 2015, that assessed human-lion interaction and the ecology of lions exposed to anthropogenic disturbance. While human-lion conflict research experienced near-exponential growth across this time period, the number of co-authors engaged in this research changed very little (mean = 3.28, se = 0.19). Moreover, co-authors of this research tended to be affiliated with units from just three highly-related STEM disciplines (biology, wildlife management, and environmental science). Comparatively, co-authors affiliated with units in the humanities and social sciences occurred in <4% of all papers examined. Our analysis also presents a novel framework that positions human-lion conflict research as having five, not two dimensions, as has been commonly conceptualized. These dimensions include not only the human and the lion dimensions, but also the livestock, wild prey, and environmental dimensions. None of the papers that we evaluated concurrently studied all five of these dimensions to determine their impact on human-lion conflict. Furthermore, despite the fact that human-lion conflict research was primarily developed by co-authors from STEM disciplines, the most common dimension evaluated was the human dimension, requiring social science and humanities expertise. Our analysis indicates that interdisciplinarity among human-lion conflict research has historically been low. These low levels of interdisciplinarity observed from 1990-2015 however, are not representative of the ongoing efforts to develop more inclusive research teams to solve human-lion conflict. Thus, we discuss the implications of this research for the development of sustainable solutions to conserve lions and preserve human well-being and identify potential avenues forward to create more interdisciplinary prides of lion researchers.